CHEMICAL STUDY OF URINARY CALCULI - Khan, Raza M.; Shah, S.A.; Shah, Syed Humayun; Nabeela, Nabeela (Journal of Ayub Medical College Abbottabad, 1989)
ABSTRACT Of the 120 stones analysed, 54 were renal in origin, 52 were bladder stones, 2 were ureteric stones while 12 were spontaneously passed.92% (111) stones contained calcium oxalate as the main component. Of these 922%, 58.3% (70) stones were pure calcium oxalate. The male to female ratio was approximately 6:1. Peak presentation was in the 15-45 years' age group